The Dynamic of Consumer Behavior, Consumer Decision, Consumer Satisfaction on Consumer Loyality on Sipirock Coffee Jakarta - Ritonga, Wier; Ganyang, Machmed Tun (Archives of Business Research, 2020)
The reasearch aim to determine the dynamic of of Consumer Behavior, Consumer Decision, Consumer Satisfaction on Consumer Loyality on Sipirock Coffee Jakarta, the year of 2017. Many prior researchs have done by some researchers, but this research differ to prior researchs, since this research done on an etnic coffee shop that serve not only coffe but also the food related to the etnic of southern Tapanuli in North Sumatera. Beside that, the coffee shop also hold etnic live music every Friday and Saturday night, one of The culture of Batak people is sing and dancing (manortor). In this coffe shop the customer feel closed to one another as they have the same culture. For the international community, it can be used to learn about Indonesia, specially the culture of the people of north sumatera. Indonesia consist of five big islans (Sumatera, Java, Borneo, Sulawesi and Papua) and thousand small islands. Any region in North Sumatera have their own coffee, for instance Mandailing coffee, Sidikalang coffee and Sipirok coffee. The management of the coffee shop mix ethnic and modern concepts by providing wi-fi connection. Simple random sampling used in the research and quatitative aproach. Collecting data used questioner and direct observation. The population of the research is all the consumer of the coffee shop, with purpossive sampling, and the sampel is 133 ( one hundred thirty three). The result of the research, (1) consumer behavior has a significant impact on consumer loyality; (2) consumer decision to purchase has a significant impact on consumer loyality; (3) consumer satisfaction has a significant impact on consumer loyality; (4) consumer behavir has a significant impact on consumer satisfaction; (5) consumer decision to purchase has a significant impact on consumer satisfaction.